2010
DOI: 10.1002/ajhb.21111
|View full text |Cite
|
Sign up to set email alerts
|

Adrenarche in comparative perspective

Abstract: Compared to rats and macaque, in humans the energetic demands of brain development and increased production of adrenal androgens are divorced from the timing of lactation, while the timing of adrenarche and brain development are still associated. Thus the neuroprotective effects of DHEAS may protect synaptic plasticity in metabolically active parts of the brain starting approximately at the age of 7, promoting prolonged development of the human prefrontal cortex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 110 publications
0
43
0
Order By: Relevance
“…Adrenarche occurs at around the age of weaning in great apes: bonobos wean after four years [22] with increases in adrenal androgens after five years [23]; orangutans wean after seven years [24] with increases in adrenal androgens after eight years [25]. Campbell noted that increased production of adrenal androgens accompanies independence from mothers at weaning in rodents and monkeys but occurs much later than weaning in humans [26]. Early hominins were probably weaned at adrenarche as occurs in other great apes.…”
Section: Discussionmentioning
confidence: 99%
“…Adrenarche occurs at around the age of weaning in great apes: bonobos wean after four years [22] with increases in adrenal androgens after five years [23]; orangutans wean after seven years [24] with increases in adrenal androgens after eight years [25]. Campbell noted that increased production of adrenal androgens accompanies independence from mothers at weaning in rodents and monkeys but occurs much later than weaning in humans [26]. Early hominins were probably weaned at adrenarche as occurs in other great apes.…”
Section: Discussionmentioning
confidence: 99%
“…Given the neurobiological effects of DHEA and DHEAS in primates and other species (Maninger et al 2009), it has been proposed that the evolution of adrenarche extended the maturation of the human brain (Campbell 2011). If this is true, then correlations between the onset (adrenarche) of adrenal androgen secretion and brain development would be expected across NHP.…”
Section: Evolution Of Adrenarchementioning
confidence: 99%
“…It should also be recognized that adrenal androgen secretion of physiological significance is not unique to primates (Boonstra et al 2011) and may be very transient in other species (Pignatelli et al 2006). Adrenarche has been the subject of numerous reviews (Parker et al 1978, Havelock et al 2004, Campbell 2006, 2011, Nader 2007, Belgorosky et al 2008, Miller 2009, Conley et al 2011a) but seldom has the evidence for or against its occurrence in the NHP been reviewed objectively.…”
Section: Clinical Significance Of Adrenarchementioning
confidence: 99%
“…From the evolutionary perspective, it has been suggested that adrenarche is a key component of 'juvenility', a period that emerges during evolution in the late Hominids and prolongs the transition from childhood to adolescence and adult life; juvenility may serve the adaptation of body composition and metabolic status to environmental conditions (10,11). Another interesting hypothesis refers to the neuromodulatory effects of DHEAS that may help to protect more metabolically active regions of the cerebral cortex to support brain maturation in the developing prepubertal child (12).…”
Section: Introductionmentioning
confidence: 99%